SYSTEMATIC LITERATURE REVIEW: PENERAPAN PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR DALAM IMPLEMENTASI KURIKULUM MERDEKA - Faizatul Diani Ifri; Aurelia Islafina; Rahma Fauzia; Nofdi, Aqsana; Nadia Nila Sari; Laura Putri Adisti; Chandra; M. Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of Science and Social Studies (IPAS) learning at the elementary school level within the framework of the Kurikulum Merdeka (Independent Curriculum) remains inadequately synthesized in Indonesian academic literature. This study aims to systematically identify, evaluate, and synthesize evidence regarding the effectiveness of differentiated instruction in IPAS learning. The findings indicate that differentiated instruction—implemented through differentiation of content, process, product, and learning environment—consistently enhances students' learning outcomes, engagement, motivation, and creative expression in IPAS. The novelty of this study lies in its comprehensive synthesis, which specifically examines differentiated instruction within the context of IPAS and the Kurikulum Merdeka in Indonesia, while providing actionable, practical implications for elementary school teachers, researchers, and educational policymakers.